2022
DOI: 10.3390/batteries8060055
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterisation of Fibre-Reinforced All-Solid-State Electrodes and Separator for the Application in Structural Batteries

Abstract: The electrification of the air transport sector demands for an energy storage that adds as little volume and weight to the overall system as possible. Regarding this so-called structural battery, composites enable the storage of electrical energy in commonly used load bearing fibre composite structures. A structural battery composite can store electrical energy while bearing mechanical loads, thus reducing parasitic mass and volume. In this study, structural cathodes were prepared by slurry coating carbon fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The study also highlighted that the state of charge (SOC) has a significant impact on the internal resistance of the battery, affecting its overall performance [30]. Vogt et al [31] explored the production and characterization of fiber-reinforced all-solid-state electrodes using LiFePO4 and found that the material demonstrated good utilization of the active material with capacities of up to 139 mAhg -1 (see Figure 2). .…”
Section: Traditional Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also highlighted that the state of charge (SOC) has a significant impact on the internal resistance of the battery, affecting its overall performance [30]. Vogt et al [31] explored the production and characterization of fiber-reinforced all-solid-state electrodes using LiFePO4 and found that the material demonstrated good utilization of the active material with capacities of up to 139 mAhg -1 (see Figure 2). .…”
Section: Traditional Cathode Materialsmentioning
confidence: 99%
“…Specific discharge capacity of cathode half cells with a structural separator cycled at 80 °C and 0.1C. The cells with the cathode and separator compressed at a higher pressure achieved capacities of maximum 139 mAhg −1 and, therefore, the best capacities of all investigated cells (Reprinted with permission from ref [31],. Copyright 2022, Batteries-MDPI).…”
mentioning
confidence: 99%
“…The lithium-ion battery (LIB) as a reliable energy storage device has dramatically affected the world thanks to its high energy density and voltage along with its superior cycle stability. They are extensively utilized in portable devices such as cell phones and laptop computers and also in electric vehicles (EVs), which are useful to decrease environmental pollutions [3][4][5][6]. LIBs are commonly made up of a graphite anode and a transition metal oxide cathode, which are soaked in an organic electrolyte and separated by a separator [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…G − H + Li + + e − → G − Li + 0.5H 2 (4) Various strategies are employed to cover the active sites to diminish irreversible capacity loss. One of these beneficial avenues is the physical coating of graphite materials with a protective layer like a metal oxide.…”
Section: Introductionmentioning
confidence: 99%